Bahasa Indonesia Sebagai Alat Komunikasi Efektif dalam Kegiatan Administrasi Manajemen Perkantoran - Andini, Sri; Padila, Sindy; Rifdah, Sayfanah; Anifah, Rohimatun; Altsani, Syaitaqi Mochamad; Rizkyanfi, Mochamad Whilky (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research examines the effectiveness of using Bahasa Indonesia in supporting administrative communication in office management environments. The research method used is descriptive qualitative with a literature study approach from various relevant articles. The data sources used are secondary information, obtained from relevant scientific journal articles published between 2019 and 2025. The data analysis process is conducted qualitatively, by gathering, reviewing, and sorting references that are in line with the study focus, then systematically organized to produce a comprehensive and profound conclusion. The results show that proper use of the Indonesian language enhances information clarity, accelerates decision-making processes, and facilitates organizational workflow. The evaluation also indicates that consistent language training and adherence to linguistic rules significantly contribute to improving communication efficiency in the workplace. These findings highlight that strong Indonesian language competence is a crucial factor in enhancing administrative quality and human resource development within organizations